The Effect Of Service Quality On Customer Loyalty Through Customer Satisfaction As A Mediating Variable At Soetjipto Coffee Mataram - Fachrurrazzi, Fachrurrazzi; Rusminah, Rusminah; Lalu Adi Permadi (Cita konsultindo, 2025)
This study aims to analyze the effect of service quality on customer loyalty at Soejipto Coffee Mataram, with customer satisfaction as a mediating variable. In the midst of increasingly fierce competition in the coffee shop industry, understanding the factors that influence customer satisfaction and loyalty is very important. Data was collected through a survey of Soejipto Coffee customers. The research method used is quantitative with an associative approach. Data were collected through surveys and analyzed using path analysis. The results showed that service quality has a positive and significant effect on customer satisfaction, which in turn increases customer loyalty. Hypothesis testing shows that all hypotheses are accepted, confirming that improving service quality will increase customer satisfaction and loyalty.